Report on the Technical Assistance Evaluation Mission to the People's Republic of China. (Policy Papers; Policy Paper, 2009)
As part of the IMF Statistics Department (STA)' s program to evaluate its technical assistance (TA) and training provided to member countries, and with the support of the Chinese authorities and the Fund's Asia and Pacific Department (APD), a TA/training evaluation mission visited China during March 16-20, 2009. The objectives of the mission were to: (1) evaluate the effectiveness of STA's TA and training to China during the period 2003-2008; (2) elicit China's views on how to broaden and enhance the technical cooperation between STA and China; (3) consider the role of the General Data Dissemination System (GDDS) in support of China's statistical development; and (4) discuss TA and training priorities for the next two years.